2021
DOI: 10.1093/aob/mcab120
|View full text |Cite
|
Sign up to set email alerts
|

Integrating terrestrial laser scanning with functional–structural plant models to investigate ecological and evolutionary processes of forest communities

Abstract: Background Woody plants (trees and shrubs) play an important role in terrestrial ecosystems, but their size and longevity make them difficult subjects for traditional experiments. In the last 20 years Functional-Structural Plant Models (FSPMs) have evolved: they consider the interplay between plant modular structure, the immediate environment and internal functioning. However, computational constraints and data deficiency have long been limiting factors in a broader application of FSPMs, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 216 publications
0
4
0
Order By: Relevance
“…Reconstruction methods such as quantitative structural models (QSMs; see Figure 1a,b) allow the measurement of fine‐scale structural details such as twigs, leaves and branches, and how they change through time, from TLS data (Kaasalainen et al, 2014; Raumonen et al, 2013; Wilkes et al, 2021). Furthermore, such data enable new ways to explicitly test theories on crown resource optimisation, light use efficiency and self‐shading (Niinemets & Anten, 2009) and pair these to structural‐functional plant models (O'Sullivan et al, 2021), leading to new knowledge of structural trade‐offs complimentary to well‐established leaf and wood economics spectra (Verbeeck et al, 2019). Very high‐resolution reconstructions of single trees that reliably preserve fine‐scale internal structure may also open new avenues of research to understand the fundamental relationships between genetics, plant morphogenesis and architecture, including testing theories of nested levels of architectural organisation (Barthélémy & Caraglio, 2007), revisiting geometric theories of plant architectural growth (Godin et al, 1999), and improving understanding genetic controls on branching architecture in woody plants (Teichmann & Muhr, 2015).…”
Section: Sensing the Individual: Morphology Foliage Crowns And Biomassmentioning
confidence: 99%
“…Reconstruction methods such as quantitative structural models (QSMs; see Figure 1a,b) allow the measurement of fine‐scale structural details such as twigs, leaves and branches, and how they change through time, from TLS data (Kaasalainen et al, 2014; Raumonen et al, 2013; Wilkes et al, 2021). Furthermore, such data enable new ways to explicitly test theories on crown resource optimisation, light use efficiency and self‐shading (Niinemets & Anten, 2009) and pair these to structural‐functional plant models (O'Sullivan et al, 2021), leading to new knowledge of structural trade‐offs complimentary to well‐established leaf and wood economics spectra (Verbeeck et al, 2019). Very high‐resolution reconstructions of single trees that reliably preserve fine‐scale internal structure may also open new avenues of research to understand the fundamental relationships between genetics, plant morphogenesis and architecture, including testing theories of nested levels of architectural organisation (Barthélémy & Caraglio, 2007), revisiting geometric theories of plant architectural growth (Godin et al, 1999), and improving understanding genetic controls on branching architecture in woody plants (Teichmann & Muhr, 2015).…”
Section: Sensing the Individual: Morphology Foliage Crowns And Biomassmentioning
confidence: 99%
“…Ideally, such data are collected over time, allowing temporal dynamics to be captured. Non‐invasive and non‐destructive quantification of these traits is therefore preferred, and this is where remote‐sensing techniques can play an important role (O'Sullivan et al, 2021). For example, Perez et al (2022) suggested that integrating lidar‐derived shoot architectural parameters of oil palm with an FSP model can help quantify shoot allometry in relation to neighbourhood competition intensity.…”
Section: Inferring Individual‐level Interactions With Close‐range Rem...mentioning
confidence: 99%
“…The laser scanning systems commonly used to collect forestry information can be divided into the following categories depending on the carrier platform: terrestrial laser scanning (including terrestrial laser, backpack laser, and vehicle-borne laser), satellite lidar scanning, and airborne laser scanning. Among them, terrestrial laser scanning systems are widely used in forest remote sensing because of their high flexibility and portability and good point cloud quality [14][15][16][17][18]. The datasets we collected in this paper are based on terrestrial laser scanning.…”
Section: Introductionmentioning
confidence: 99%